2022
DOI: 10.1155/2022/4133237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pulmonary Rehabilitation on Postoperative Clinical Status in Patients with Lung Cancer and Chronic Obstructive Pulmonary Disease: A Systematic Review and Meta-Analysis

Abstract: Pulmonary rehabilitation (PR) has a curative effect in patients undergoing pneumonectomy for lung cancer. Nevertheless, the contribution of PR to the clinical status of patients with chronic obstructive pulmonary disease (COPD) undergoing lung resection has not been adequately elucidated. The aim of this systematic review of randomized and nonrandomized controlled trials was to appraise the impact of PR compared to conventional treatment based on postoperative clinical status in patients with lung cancer and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…The findings of this study are in agreement with the previous reviews that have also demonstrated a significant impact of pulmonary rehabilitation nursing intervention on reducing postoperative pulmonary complication. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study are in agreement with the previous reviews that have also demonstrated a significant impact of pulmonary rehabilitation nursing intervention on reducing postoperative pulmonary complication. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…This proves that our nursing pulmonary rehabilitation program has a wholesome effect on the patients' postoperative outcomes positively affecting their physical, social and mental health. However, previous studies found no significant improvement in the quality of life postoperatively following a pulmonary rehabilitation program [17][18][19][20][21] intensity being of key importance. Nevertheless, in these patients extreme breathlessness and/or peripheral muscle fatigue may prevent patients from higher levels of intensity.…”
Section: Discussionmentioning
confidence: 99%
“…17 Indeed, trials exploring the effectiveness of such a program amongst patients with lung cancer reported such findings. [18][19][20][21] We cannot make conclusions about the quality of life on the basis of our results given the differences in the tools, intervention designs, and/or extent of the surgical operations in the different relevant studies. We used the EQ-5D, which is a worldwide standard tool for measuring quality of life; and, the questionnaire has been validated for use and a valuation set for our country is available.…”
Section: Discussionmentioning
confidence: 99%
“…After enrolment, patients in all groups participated in a multidisciplinary conventional inpatient rehabilitation program on the day of admission and day before surgery, and the program was standardised using evidence from systematic reviews and mainly included exercise, education, nutritional, respiratory physiotherapy, and psychological counselling [ 27 , 28 ]. All participants were provided information and instructions regarding perioperative management.…”
Section: Methodsmentioning
confidence: 99%